Empirical Verification of the Model of the Knowledge Orientation of a Company - Rószkiewicz, Małgorzata; Więziak-Białkowska, Dorota (Model orientacji na wiedzę przedsiębiorstwa - empiryczna weryfikacja, 2011)
The paper aims at empirical verification of the conceptual model of the knowledge orientation of a company. The model illustrates the relations among managers’ knowledge orientation, the company’s knowledge orientation and the economic performance of a company. The model is empirically verified using the structural equation modelling. The results obtained prove that the model needs modifications. Nevertheless, in our research it is proved that the managers’ knowledge orientation influences significantly and positively the knowledge orientation of a company and the latter is one of the determinants of the economic performance of a company.
Keywords: wiedza; wiedza w organizacji; przedsiębiorstwo; knowledge; knowledge in organization; enterprises